EGFR exon 20 insertions in advanced non-small cell lung cancer: A new history begins - Remon, Jordi; Hendriks, Lizza E.L.; Cardona, Andres F.; Besse, Benjamin (Cancer treatment reviews, 2020)
•EGFR exon 20 insertion mutations occur in ~2–3% of all NSCLC cases.•Activity of 1st to 3rd generation EGFR-TKI is less in EGFR ex20ins versus common mutations.•Osimertinib might play a role in the treatment of EGFR ex20ins mutations.•Poziotinib, mobocertinib and amivantamab are promising new EGFR ex20ins treatments.•The specific role of EGFR ex20ins variants merits further evaluation. Although targeted therapy is standard of care in a large subset of oncogenic addicted non-small cell lung cancers (NSCLC), until recently, this therapeutic approach has not been feasible for all genomic alterations such as for those tumors harboring Epidermal Growth Factor Receptor (EGFR) exon 20 insertion (ex20ins) mutations. Despite being the third most common EGFR mutation, a limited efficacy of first- and second-generation EGFR tyrosine kinase inhibitors (TKI) exists. This is related to the heterogeneity at the molecular level in EGFR ex20ins mutation variants and the finding that this mutation promotes active kinase conformation but does not increase the affinity for EGFR TKI. As a result, the prognosis of this population is diminished. Therefore, chemotherapy remained the most suitable strategy in this subset of EGFR mutant NSCLC patients. Recently, new treatment strategies have been reported in this landscape, either with new EGFR TKI or bispecific antibodies, which may establish a new standard of care in the coming future for these patients. Future research should focus on elucidating the oncogenic degree of all EGFR ex20ins variants, the potential role of combination strategies either with chemotherapy or immune checkpoint inhibitors, and the most appropriate first-line treatment strategy in this subgroup. Finally, the knowledge of mechanisms of acquired resistance to these new agents upon progression is a priority for personalising treatment at that time. It is in this framework, that we provide a thorough overview on this subject.